Laparoscopic appendicectomy under spinal anesthesia, a cost effective and efficient approach - Jain, Sarvesh; D, Rohit; L, Nety; Shashibala, Shashibala (Public Health Review: International Journal of Public Health Research, 2017)
Introduction: Appendicitis is common surgical emergency in developing countries. One out of every 2000 people has an appendicectomy sometime during their lifetime. It can be done by open method or by laparoscopic method. Open method leads to long hospital stay and more chances of infection. On the other hand laparoscopy has advantage of shorter hospital stay, less pain and better cosmetic results. Objective: Laparoscopic appendicectomy can be done under general anaesthesia or spinal anaesthesia. General anaesthesia is costly and has its own complication. Use of spinal anesthesia is increasing day by day for laparoscopic procedure because of cost effectiveness and less complication rate, appendicectomy is common procedure which is perform laparoscopically in our set up. Objective of this study was to evaluate feasibility of laparoscopic appendicectomy under spinal anaesthesia. Method: This prospective observational study was conducted in Bundelkhand Medical College Hospital from August 2015 to March 2017. We have chosen 50 patients of laparoscopic appendicectomy (LA) for our study. All patients were explained about appendicectomy and spinal anaesthesia in detail. We prefer spinal anaesthesia (SA) over general anaesthesia (GA) despite of common practice of general anaesthesia for all laparoscopy. All were given injection midazolam, pentazocin and ketamine (MPK) after spinal anaesthesia but before pneumoperitonium. Result: None of them were required to convert to general anaethsesia with endotracheal intubation or open surgery. All tolerated the procedure well. Conclusion: So it can be concluded that it is cost effective and efficient approach